Authentic examination papers (Cambridge, 2019)
IELTS academic and to practice examination techniques using authentic tests. An introduction to these modules is included in the book, together with an explanation of the scoring system used by Cambridge English Language Assessment. There is a comprehensive section of answers and tapescripts at the back of the book.
Keywords: Tiếng Anh,English language; Kiểm tra, câu hỏi, v.v.,Examinations, questions, etc